How to perform solah with upper limb injuries - Mohamed Amin, Mohamed Azril; Siron @ Baharom, Khairul Nizam; Goh, Kian Liang (2013)
Solah is one of the Five Pillars of Islam. The task of performing solah is of utmost importance for all Muslims. The order of performing solah was bestowed directly to Prophet Muhammad S.A.W during Israk Mikraj. This highlights the greatest priority of performing solah even in injurious conditions. In patients with upper limb injuries and limited function, solah is compulsory and must be performed with any remaining physical functions. A group of undergraduate medical students researched and discussed the correct method of performing ablution and solah in injured patients with a facilitator from Kulliyyah of Islamic Revealed Knowledge, IIUM. The issues discussed were the options available in performing ablution prior to solah which either was with water, tayammum (dust), or both. The method of performing solah in upper limb injuries was highlighted. We conclude that the tayammum is the most practical and feasible ablutions method for patients with upper limb injuries prior to perform solah.